Deployable linear-to-circular polarizer using PDMS based on unloaded and loaded circular FSS arrays for pico-satellites - Mirza, H.; Hossain, T. M.; Soh, Ping Jack; Jamlos, M. F.; Ramli, M. N.; Al-Hadi, A. A.; Hassan, E. S.; Yang, S. (IEEE, 2019)
In this paper, flexible and deployable double-sided linear-to-circular polarizers designed on polydimethylsiloxane are proposed for the first time to the best of our knowledge. ShieldIt textile is used as the conducting element of the two designs based on two different unit cell arrays: a loaded circular patch unit cell or an unloaded circular patch unit cell, both backed by a generic rectangular element on its reverse side. This is in contrast to conventional frequency-selective structure-based linear-to-circular polarizers implemented using rigid substrates, which are multi-layered and requires inter-layer physical spacing. This complicates their implementation using flexible substrates and in a deployable format. Upon implementation of this double-sided polarizer, their final performances are evaluated in terms of the phase difference, conversion efficiency, 3-dB axial ratio (AR), and ellipticity bandwidth (from 40° to 45°). Measurements indicated good agreements with simulations, and both structures exhibited more than 90% of conversion efficiency from 2.34 to 3 GHz (for the loaded circular unit cell) and from 2.36 to 3 GHz (for the unloaded circular unit cell). In terms of ellipticity, a bandwidth of 8.67% is observed for the unloaded design and 13.82% for the loaded design. The unloaded structure exhibited a fractional 3-dB AR bandwidth of 36.36% (from 1.98 to 2.86 GHz) in simulations, and 32.64 % (from 2.00 to 2.78 GHz) when evaluated experimentally. Conversely, the loaded design showed only 12.58%. An equivalent circuit model is proposed and validated via a comparison between the circuit and full-wave simulations. Finally, the performances of these polarizers are also assessed under different bending conditions due to the use of flexible materials, prior to the proposal of a suitable deployment mechanism.